Transformational Leadership And Work Stress On Employee Productivity : The Mediating Role Of Job Satisfaction At Pegadaian Dinoyotangsi Surabaya Branch Office - Mohamad Dzul Hilmi; Hujjatullah Fazlurrahman (International Journal of Social, Economic, and Business, 2024)
This study aims to examine and analyze the effect of transformational leadership and work stress on employee productivity through job satisfaction as a mediator among employees at PT. Pegadaian Cabang Pembantu Dinoyotangsi Surabaya. The sampling technique used is saturated sampling with a total of 49 respondents. The statistical analysis used in this study is SEM (Structural Equation Modeling) and PLS (Partial Least Square) with the aid of SmartPLS4 software. The results of this study explain that transformational leadership has a positive and significant effect on employee productivity. Work stress does not have an effect on employee productivity. Job satisfaction has a positive and significant effect on employee productivity. Transformational leadership has a positive and significant effect on job satisfaction. Work stress does not have an effect on job satisfaction. Job satisfaction mediates the relationship between transformational leadership and employee productivity. Job satisfaction does not mediate the relationship between work stress and employee productivity.